AN ANALYTICAL STUDY ON THE FLOOR PLANS OF STEVEN HOLL'S RESIDENTIAL PROJECTS - Yurika Mori; Bart Dewancker (Journal of Architecture&ENVIRONMENT, 2022)
Steven Holl, an American architect who began his design career in 1975, has a unique way of designing. He is known for his many drawings, artistic expression, and distinctive conceptual designs. Steven Holl's designs start with watercolour sketches, a world-renowned architect whose projects are still underway worldwide. This study will examine the philosophy of Steven Holl's plan. It will also explore the aspects of his proposal of sustainable architecture, which he has presented in recent years. It will consider the coexistence of the theme of sustainable architecture with the works of contemporary architects to deepen our knowledge of architectural DesignDesign. In addition, the purpose is to clarify the modelling characteristics by classifying the outer shape of residential works using a plan view.